Analisis Kelayakan Finansial Pengembangan Gedung Dormitory Di Politeknik Astra - Cintri Anjani Rahmada Putri; Oei Fuk Jin (Jurnal Karajata Engineering, 2025)
The high demand for dormitories at Astra Polytechnic will keep rising in tandem with the growing student body. Investment for another tower building is required and also will have an impact on dormitory rental prices. The purpose of this study is to find out the evaluation of the feasibility of building a new dormitory building in terms of financial aspects and to calculate the appropriate dormitory room rental price for the dormitory building using a forecasting method. The research results show that the project is declared financially feasible because the IRR value is greater than the MARR, which is 7.8% > 6.875%, and the payback period is 19.38 years. The results were obtained with an adjusted rental price, where rental rates increase by 10% per year from the second to the fifth year. Following the development of the second dormitory tower in the sixth year, rental prices must increase by 20% annually until the end of the investment period in the 20th year